Localized and metastatic myxoid/round cell liposarcoma12. Issue 10 (7th February 2013) - Hoffman, Aviad; Ghadimi, Markus P. H.; Demicco, Elizabeth G.; Creighton, Chad J.; Torres, Keila; Colombo, Chiara; Peng, Tingsheng; Lusby, Kristelle; Ingram, Davis; Hornick, Jason L.; Wang, Wei‐Lie; Ravi, Vinod; et al.
Abstract BACKGROUND. Myxoid liposarcoma (MLPS), a disease especially of young adults with potential for local recurrence and metastasis, currently lacks solid prognostic factors and therapeutic targets. The authors of this report evaluated the natural history and outcome of patients with MLPS and commonly deregulated protein biomarkers. METHODS. Medical records were retrospectively reviewed for patients who presented to the authors' institution with localized (n = 207) or metastatic (n = 61) MLPS (1990 to 2010). A tissue microarray of MLPS patient specimens (n = 169) was constructed for immunohistochemical analysis of molecular markers. RESULTS. The 5‐year and 10‐year disease‐specific survival rates among patients with localized disease were 93% and 87%, respectively; male gender, age >45 years, and recurrent tumor predicted poor outcome. The local recurrence rate was 7.4%, and the risk of local recurrence was associated with recurrent tumors and nonextremity disease location. Male gender was the main risk factor for metastatic disease, which occurred in 13% of patients. Forty percent of patients who had localized disease received chemotherapy, mostly in the neoadjuvant setting. Immunohistochemical analysis revealed significantly higher expression of C‐X‐C chemokine receptor type 4 (CXCR4) and platelet‐derived growth factor beta (PDGFR‐β) in metastatic lesions versus localized lesions. Tumors with a round cell phenotype expressed increased levels of CXCR4, p53, adipophilin, PDGFR‐α, PDGFR‐β, and vascular endothelial growth factor relative to myxoid phenotype. Only the receptor tyrosine kinase encoded by the AXL gene (AXL) was identified as a prognosticator of disease‐specific survival in univariate analysis. CONCLUSIONS. In this study, the authors identified clinical and molecular outcome prognosticators for patients with MLPS as well as several potential therapeutic targets. Cancer 2013. © 2013 American Cancer Society.